Motor performance of young soccer players depending on biological age - Miroslav Holienka; Matej Babic; Ladislava Doležajová; Peter Šelinger; Eva Musilová (University of Novi Sad, Faculty of Sport and Physical Education, 2017)
The main purpose of our article was to broaden the knowledge of the level of the motor performance of young soccer players in puberty, taking into account their biological age. The object of our research was 18 soccer players in the U 15 category of the soccer club ŠK Slovan Bratislava divided into a subset with accelerated development (n=10) with body height 177,4 ± 5,1 cm, body weight 65,8 ± 7,5 kg and a subset with retarded development (n=8) with body height 170,9 ± 7,3 cm, body weight 63,9 ± 7,7 kg. To assess the motor performance, a set of 3 tests to evaluate speed and speed-coordination (agility) capabilities was applied. The set of tests contained a 10 m run (n=10 - average value of 1.61 s, n=8 - average value of 1.62 s), a 30 m run (n=10 - average value of 4.13 s, n=8 - average value of 4.16 s) and a 5 x 10 m run with a change of direction (n=10 - average value of 11.55 s, n=8 - average value of 11.70 s). Using the Mann-Whitney U test, we did not confirm in our case a statistically significant different level in the motor performance of the monitored sets with regard to the degree of their biological maturity.